Haematology parameters of West African dwarf rams fed velvet bean (mucuna pruriens) ensiled with whole maize stover (2015)
The haematological characteristics of West African Dwarf (WAD) Rams fed velvet bean (Mucuna pruriens) foliage ensiled with whole maize were determined. Twenty (20) growing rams aged 10-15 months with mean weight ranging between 11.75-12.00kg were randomly assigned to four dietary treatments comprising five animals per dietary treatment in a completely randomized design (CRD). Treatment 1 contained 100% ensiled whole maize, Treatment 2 contained 75% whole maize + 25% Mucunapruriensfoliage silage, Treatment 3 contained 50% whole maize + 50% Mucunapruriensfoliage silage, Treatment 4 contained 25%> whole maize + 75% Mucunapruriensfoliage silage respectively. Each animal receive each diet at 5% body weight for 105 days. Blood was collected through jugular vein and put into well lebelled bottle containing anticoagulant ethylene diaminetetracetic acid (EDTA). The blood samples were analyzed for Red blood cell (RBC) count, Parked cell volume (PCV), haemoglobin (Hb), white blood cell (WBC) count, neutrophils, lymphocytes, eosinophils and monocytes. Significant differences (P<0.05) were obtained in haemoglobin and neutrophil which range from 6.11-9.87g/dl and 35.28 - 41.23% respectively while other parameters investigated showed no significant (P>0.05) differences. The nutritional health status of the rams can be enhanced when fed Mucunapruriensfoliage and whole maize silage but best result could be obtained when fed silage containing 75% whole maize and 25% Mucunapruriens.